Readability Analysis of Pancasila and Citizen Education Textbooks in The Curriculum Merdeka: Challenges and Opportunities in Developing 21st Century Skills - Syukron Saputra; Rayhan Witra Pratama; Randa Gustiawan; Mirawati Mirawari (International Journal of Applied Counseling and Social Sciences, 2025)
This study aims to analyze the readability level of Pancasila and Citizenship Education (PPKn) textbooks under the Independent Curriculum and assess their contribution to supporting the development of 21st-century skills. The focus of the study was directed at two PPKn textbooks used in Kerinci Regency, namely those published by the Indonesian Curriculum and Book Center, and Srikandi Empat. The study used a quantitative approach with a content analysis method with a questionnaire instrument to assess three indicators of readability, namely ease of use, interestingness, and 21st-century skills. The results showed that the textbooks published by the Curriculum and Book Center and Srikandi Empat were in the Sufficient category because there were weaknesses in the aspects of increasing reading interest, sentence structure, and communication activities. Both textbooks support 21st-century skills, especially critical thinking, creativity, and collaboration, but communication skills still need to be strengthened. Overall, the PPKn textbooks under the Independent Curriculum have demonstrated learning that is relevant to the demands of the 21st century, although several aspects need to be improved to make the books more effective